2022
DOI: 10.3389/fnagi.2022.845825
|View full text |Cite
|
Sign up to set email alerts
|

Does Cognitive Training Improve Mobility, Enhance Cognition, and Promote Neural Activation?

Abstract: A close inter-relationship between mobility and cognition is reported in older adults, with improvements in gait performance noticeable after cognitive remediation in frail individuals. The aim of this study was to evaluate the efficacy of computerized cognitive training (CCT) on mobility in healthy, independently living older adults, and to determine whether CCT is associated with changes in neural activation for mobility-related brain processes. Using a randomized single-blind control design, sixty-three non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…What non-pharmacological interventions may effectively prevent dual decline? Some non-pharmacological studies may prevent dual decline but empirical data are needed, such as transcranial direct current stimulation studies, 27 cognitive training, cognitive stimulation/engagement training, [28][29][30][31][32][33][34] blood pressure management, 35 dietary restriction, weight loss, and increased physical activity. 36,37 45 Preliminary results from the anti-amyloid antibody Lecanemab trial show positive effects on both primary and secondary outcomes of dementia.…”
Section: Respond To the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…What non-pharmacological interventions may effectively prevent dual decline? Some non-pharmacological studies may prevent dual decline but empirical data are needed, such as transcranial direct current stimulation studies, 27 cognitive training, cognitive stimulation/engagement training, [28][29][30][31][32][33][34] blood pressure management, 35 dietary restriction, weight loss, and increased physical activity. 36,37 45 Preliminary results from the anti-amyloid antibody Lecanemab trial show positive effects on both primary and secondary outcomes of dementia.…”
Section: Respond To the Problemmentioning
confidence: 99%
“…What non‐pharmacological interventions may effectively prevent dual decline? Some non‐pharmacological studies may prevent dual decline but empirical data are needed, such as transcranial direct current stimulation studies, 27 cognitive training, cognitive stimulation/engagement training, 28–34 blood pressure management, 35 dietary restriction, weight loss, and increased physical activity 36,37 . Specific studies, such as social dance, computerized brain games, Experience Corps, and the ACTIVE (Advanced Cognitive Training for Independent and Vital Elderly) trial, were discussed at the workshop.…”
Section: What Are the Questions To Be Addressed And What Does The Fie...mentioning
confidence: 99%
“…Given the benefits of computerized cognitive training (CCT) in slowing cognitive decline among older adults with neurocognitive disorders and its cognitively stimulating effects among cognitively unimpaired older adults (7)(8)(9), CCT that targets frontal lobe and improves executive function might be a promising treatment for LLD (10,11). Compared to existing interventions, CCT is standardized, structured, repeatable, more accessible and cost-effective than psychotherapy, allows monitoring of adherence, can be tailored to individual skill level as a form of personalized medicine, and does not have concerns for drug side-effect or drug-drug interaction (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Computerized cognitive training programs include tasks and games that target specific cognitive processes, such as executive functions and memory [17]. Given the contribution of executive functions to gait speed and performance [18], it has been proposed that CCT could also benefit mobility outcomes such as usual gait speed and dual-task gait speed [19,20]. A systematic review and metaanalysis of 10 randomized controlled trials showed a small effect of cognitive-based interventions on dualtask gait speed [21], but not usual gait speed, and concluded additional studies are needed.…”
Section: Introductionmentioning
confidence: 99%